Exploring the critical factors influencing online examinations - Jayasundara, J.M.A.M.; Rajapaksha, C.; Jayasiri, A. (Colombo : Sri Lanka Association for the Advancement of Science, 2021)
With the outbreak of the Covid-19 pandemic, there are less options to conduct examinations physically and most of the universities in Sri Lanka started conducting online examinations. Yet researchers have assessed the online examinations throughout the pandemic, there is only a few research done to evaluate the current state of practices in this field. This study investigates the critical factors influencing online examinations in higher education, predominantly as a case analysis in the Sri Lankan context. Based on the systematic review of literature, the empirical and practice gaps were identified and based on the discoveries of this research, the critical factors that influence the online examinations were identified as the perception of educators, perception of students, pedagogical alignment of examinations, availability and the affordability of the technology and country’s resource position. From these factors, a conceptual model has been developed and the inter-relationships among them were also identified. Research data are collected through online surveys from postgraduates and undergraduates, (a sample of 80) who have faced at least one online exam, interviews (20 interviews) with educators and technical experts in the field, and resource persons of the “Nenasala” center. A mixed-method approach was used to analyze both qualitative and quantitative data. Students’ perception, educators’ perception, and the pedagogical alignment regarding online exams have been explored thus, outlined complications and suggested implications can be used when steering the online exams. Furthermore, the feasibility of conducting online exams at “Nenasala” centers has been explored for the students who have various issues, and the student’s willingness to do so has been also evaluated in this study. Moreover, the current state of technologies that are being used by state universities in Sri Lanka has been explored and the drawbacks and suggestions were also presented in this paper. Thus, inferences from this research would be beneficial to the university community around the world to perform high-quality and trustworthy online examinations. The discoveries of this research help to comprehend and improve the current chaos and the suggestions can be used even after the pandemic period to enhance distance education.
Keywords: Online Examinations; Pedagogical Alignment; Availability Of Technology; Educators’ Perception; Students’ Perception